2004
DOI: 10.1128/aem.70.9.5274-5282.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Extracellular Proteins of Enterohemorrhagic and Enteropathogenic Escherichia coli Strains and Their ihf and ler Mutants

Abstract: Enterohemorrhagic and enteropathogenic Escherichia coli (EHEC and EPEC, respectively) strains are closely related human pathogens that are responsible for food-borne epidemics in many countries. Integration host factor (IHF) and the locus of enterocyte effacement-encoded regulator (Ler) are needed for the expression of virulence genes in EHEC and EPEC, including the elicitation of actin rearrangements for attaching and effacing lesions. We applied a proteomic approach, using two-dimensional polyacrylamide gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 45 publications
3
51
0
1
Order By: Relevance
“…A number of omptin family members have been implicated in virulence, including Pla from Yersinia pestis and NspA from Neisseria meningitidis (21). The Z3065 protein was previously identified in the culture supernatant of EHEC grown in the tissue culture medium DMEM (29). The Z3065 protein is 99% identical to YodA from E. coli K-12, and the Z3065 gene and yodA are flanked by the same genes in their respective genomes.…”
Section: Resultsmentioning
confidence: 99%
“…A number of omptin family members have been implicated in virulence, including Pla from Yersinia pestis and NspA from Neisseria meningitidis (21). The Z3065 protein was previously identified in the culture supernatant of EHEC grown in the tissue culture medium DMEM (29). The Z3065 protein is 99% identical to YodA from E. coli K-12, and the Z3065 gene and yodA are flanked by the same genes in their respective genomes.…”
Section: Resultsmentioning
confidence: 99%
“…Proteomic analysis has become increasingly important, allowing global analysis of protein expression patterns and providing a better understanding of physiological changes related to various genetic and/or environmental conditions (Li et al, 2004;Sanchez et al, 2005;Weber et al, 2006;Xia et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that the master positive regulator of LEE genes, as well as of genes located outside the LEE, is the LEE-encoded regulator (Ler), whose main function is to counteract the repression exerted by H-NS on these genes (1,3,9,17,23,39,48,57,62,65,69). It has also been reported that Ler represses its own expression in a concentration-dependent fashion (4) and that it can also act as a negative regulator for other genes outside the LEE (1,61).…”
mentioning
confidence: 99%